Sum of reciprocals.

Level pending

For the equation of the form: a x 2 + b x + c = 0 ax^2+bx+c=0 ,determine

1 x 1 + 1 x 2 \frac{1}{x_1}+\frac{1}{x_2} where x 1 x_1 and x 2 x_2 are the roots if a = 5 a=5 , b = 3 b=3 and c = 1 c=-1 .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Prasun Biswas
Feb 3, 2014

We shall here use the quadratic formula to find the roots x 1 x_{1} and x 2 x_{2} .

According to the formula, if a quadratic equation is in the form a x 2 + b x + c = 0 ax^{2}+bx+c=0 and has its discriminant ( D ) = b 2 4 a c 0 (D)=b^{2}-4ac \geq 0 , then the equation has real roots and the roots are = b ± D 2 a =\large{\frac{-b\pm \sqrt{D}}{2a}} .

Here, it is said that the equation is in a x 2 + b x + c = 0 ax^{2}+bx+c=0 form with a = 5 , b = 3 , c = ( 1 ) a=5,b=3,c=(-1) , so discriminant ( D ) = 3 2 4 × 5 × ( 1 ) = 9 + 20 = 29 0 (D)=3^{2}-4\times 5\times (-1)=9+20=29 \geq 0 , so the equation has real roots.

So, the roots are = 3 ± 29 2 × 5 = 3 ± 29 10 =\large{\frac{-3\pm \sqrt{29}}{2\times 5} = \frac{-3\pm \sqrt{29}}{10}}

So, let us take x 1 = 3 + 29 10 x_{1}=\large{\frac{-3+\sqrt{29}}{10}} and x 2 = 3 29 10 x_{2}=\large{\frac{-3-\sqrt{29}}{10}}

Then, 1 x 1 + 1 x 2 = 10 3 + 29 + 10 3 29 = 10 ( 3 29 3 + 29 ) 9 29 = 10 × ( 6 ) ( 20 ) = 3 \large{\frac{1}{x_1}+\frac{1}{x_2}=\frac{10}{-3+\sqrt{29}}+\frac{10}{-3-\sqrt{29}} = \frac{10(-3-\sqrt{29}-3+\sqrt{29})}{9-29}=\frac{10\times (-6)}{(-20)}=\boxed{3}}

At the last, I didn't show the rationalization properly, so I am showing it here in the comment. First you should know the identity ( a + b ) ( a b ) = a 2 b 2 (a+b)(a-b)=a^2-b^2 . Here is the rationalization :

10 3 + 29 + 10 3 29 \large{\frac{10}{-3+\sqrt{29}}+\frac{10}{-3-\sqrt{29}}}

= 10 ( ( 3 29 ) + ( 3 + 29 ) ) ( 3 + 29 ) ( 3 29 ) =\large{\frac{10((-3-\sqrt{29})+(-3+\sqrt{29}))}{(-3+\sqrt{29})(-3-\sqrt{29})}}

= 10 ( 3 29 3 + 29 ) ( 3 + 29 ) ( 3 29 ) =\large{\frac{10(-3-\sqrt{29}-3+\sqrt{29})}{(-3+\sqrt{29})(-3-\sqrt{29})}}

= 10 × ( 6 ) ( 3 ) 2 ( 29 ) 2 =\large{\frac{10\times (-6)}{(-3)^2-(\sqrt{29})^2}}

= 10 × ( 6 ) 9 29 =\large{\frac{10\times (-6)}{9-29}}

And the rest is done in the given solution.

Prasun Biswas - 7 years, 4 months ago

You could simply use Vieta's Formula.

Harsh Shrivastava - 6 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...